Dental aspects of sweet snacks in a modern diet. - JARDINE, N.J. (1997)
Reviews the mechanism of decay in tooth enamel, the difficulties of classifying food by cariogenicity and the significance of eating paterns, saliva production and fluoridation. Agrees with WHO guidelines that sugar plays a minor role in caries causation where fluoride and hygenic measures have been taken.